Endowments, expectations, and the value of food safety certification: experimental evidence from fish markets in Nigeria - Shikuku, Kelvin Mashisia; Bulte, Erwin; Lagerkvist, Carl Johan; Nhuong Tran (Cambridge University Press, 2023)
We study the impact of endowments and expectations on reference point formation and measure the value of food safety certification in the context of fish trading on real markets in Nigeria. In our field experiment, consumers can trade a known food item for a novel food item that is superior in terms of food safety––or vice versa. Endowments matter for reference point formation, but we also document a reverse endowment effect for a subsample of respondents. The effect of expectations about future ownership is weak and mixed. While expectations seem to affect bidding behavior for subjects “trading up” to obtain the certified food product (a marginally significant effect), it does not affect bids for subjects “trading down” to give up this novel food item. Finally, willingness to pay for safety certified food is large for our respondents—our estimate of the premium is bounded between 37 and 53% of the price of conventional, uncertified food.